Factors influencing in vitro growth of two Cameroon isolates of Beauveria bassiana and Metarhizium anisopliae – candidates for development of mycoinsecticides against agricultural pests in Cameroon - Membang, G.; Hanna, R.; Mahot, H.C.; Fotso Kuate, A.; Kumar, P.L.; Fiaboe, K.K.M.; Masso, C.; Ambang, Z. (Informa UK Limited, 2025)
Insect pathogenic fungi show promise for agricultural pest control, but effective biopesticide formulation requires strains resilient to environmental stressors. Two Cameroonian isolates-Metarhizium anisopliae MIITAC11.3.4 and Beauveria bassiana BIITAC6.2.2) were previously evaluated for their potential as mycoinsecticides against pests like banana borer, cocoa mirid, flea beetle, and banana aphid. This study assessed their responses to pH, photoperiods, exposure durations under UVB radiation, and ambient relative humidity levels on colony formation, mycelial growth, and conidial production. Both isolates exhibited broad pH tolerance (3-13), though pH 3 inhibited mycelial growth but not sporulation. The optimum ranges 4-12 depending on biological traits. Photoperiods affected mostly mycelial growth and pigmentation. Under UV exposure, B. bassiana remained viable after 45 minutes, while M. anisopliae failed to grow belong this exposure time even with 6 days extension in incubation chamber. Moreover, a 30-minute UV pulse under UVtransilluminator at wavelength 320 nm enhanced mycelial growth and conidial production in B. bassiana but only mycelial growth in M. anisopliae. Both fungi thrived across a wide humidity range (30–99%), with optimal growth at 50–75% relative humidity. These findings highlight the isolates’ adaptability to varying conditions, crucial for mass production and field application. Beauveria bassiana demonstrated greater UV resistance, making it potentially more suitable for sun-exposed environments, while M. anisopliae may require protective formulations. The study provides key insights for optimising fungal biopesticide production, ensuring efficacy against target pests under diverse agricultural conditions.